Leaf Nitrogen content in oil palm seedlings and their relationship to SPAD chlorophyll meter readings - Law, C. C; Abdul Rahman, Zaharah; Mohd Hanif, Ahmad Husni; Abdullah, Siti Nor Akmar (Malaysian Palm Oil Council, 2014)
The SPAD chlorophyll meter is a useful tool to assess Nitrogen (N) fertilizer requirement for many field crops with the advantages of rapid and in-field crop N status measurement. The objective of this study was to provide a direct comparison between SPAD meter readings versus leaf N concentrations in oil palm seedlings. Nine genotypes of oil palm were subjected to N stress conditions and then followed by N recovery. SPAD readings and the leaf N concentrations were measured to monitor the oil palm recovery responses induced by the stress condition. Based on this study, all oil palm genotypes, except Genotype I, demonstrated 9 days of lag period before the SPAD readings and leaf N concentrations began to increase. Genotype A showed the fastest recovery ability compared to the other genotypes. Genotypes A and E, which inherited more genetic diversity, showed better N response on recovery as compared to the other genotypes. SPAD readings of the oil palm also showed significant (p < 0.0001) and high positive association (r = 0.7337) with leaf N concentrations. This study showed that SPAD chlorophyll meter could be used as a reliable tool to determine the N status of the oil palm seedlings.